Integrated reporting: bibliometric landscape - Serpeninova, Yuliia (Public Policy and Accounting, 2022)
The growing importance of non-financial disclosure and development of integrated reporting concept necessitates a formation of complex systematic theoretical background, in particular, by means of the bibliometric analysis. Use of special software (VOSviewer, SciVal, Publish or Perish, inbuilt database analysis tools in Scopus, Web of Science and Google Scholar; Google Trends and Google Books Ngram Viewer) expands the analytical capabilities of bibliometric analysis and helps to cover the entire array of existing papers on integrated reporting. In particular, this paper covers: the assessment of general dynamics of publications; systematisation of the chronological and regional specifics of publications; study of the thematic specifics of publications by analysing keywords, subject areas, and thematic clusters.